Introduction to the Focused Issue on Entrepreneurship - Shane, Scott (Management Science, 2006)
This article is an introduction to the focused issue on entrepreneurship. It provides motivation for greater scholarly investigation of the phenomenon of entrepreneurship, explains the evolution of the focused issue, offers an overview of the seven papers in the issue, and offers the editor’s thoughts on the relationship of the papers in the focused issue to research on entrepreneurship in general.